3-O-acetylrubiarbonol B preferentially targets EGFR and MET over rubiarbonol B to inhibit NSCLC cell growth - A-Young Nam; Sang Hoon Joo; Na Yeong Lee; Goo Yoon; Jin Woo Park; MinKyun Na; Jung-Hyun Shim (PLoS ONE, 2025)
Non-small cell lung cancer (NSCLC) is one of the leading causes of cancer-related deaths, remaining a significant challenge in terms of early detection, effective treatment, and improving patient survival rates. In this study, we investigated the anticancer mechanism of rubiarbonol B (Ru-B) and its derivative 3-O-acetylrubiarbonol B (ARu-B), a pentacyclic terpenoid in gefitinib (GEF)-sensitive and -resistant NSCLC HCC827 cells. Concentration- and time-dependent cytotoxicity was observed for both Ru-B and ARu-B. The in vitro kinase assay showed that ARu-B treatment inhibited epidermal growth factor receptor (EGFR), mesenchymal-epithelial transition (MET), and AKT1, and their phosphorylation in HCC827 cells. A molecular docking model suggested that ARu-B could interact with EGFR and MET in different ways, either by binding to the ATP pocket or the substrate pocket. ARu-B induced reactive oxygen species (ROS) generation and cell cycle arrest. The induction of apoptosis through caspase activation was confirmed by preventing cytotoxicity with Z-VAD-FMK pretreatment. Taken together, ARu-B inhibited the growth of both GEF-sensitive and GEF-resistant NSCLC cells by targeting EGFR, MET, and AKT and inducing ROS generation and caspase activation. Further studies on ARu-B can improve the treatment of chemotherapy-resistant NSCLC through the development of effective ARu-B-based anticancer agents.